Application of Large Scale Particle Image Velocimetry (LSPIV) to Identify Flow Pattern in a Channel. (2015) - Sutarto, Tommy Ekamitra
Abstract: This study has three main goals, first, to map the flow structure in a channel using a unique technique named Large Scale Particle Image Velocimetry (LSPIV). Second, to test the sensitivity of LSPIV results to LSPIV parameters (e.g., Interrogation Area, and Searching Area). Third, to test the capability of LSPIV method in predicting the magnitude and direction of flow velocity in a complex flow structure. An LSPIV system was set to observe 14 (fourteen) runs of laboratory re-circulating trapezoidal open channel with a sudden expansion-constriction shape in its middle reach. LSPIV technique was successfully mapping the core flow and the swirling motions near the wall in the expansion-constriction reach. In the core flow region, longitudinal velocity, U, estimate was sensitive to the interrogation area and searching area parameters, while lateral velocity, V, estimate was insensitive to those parameters. The opposite condition occurred in the wall region. The maximum forward flow velocityU was 0.56 m/s occurred in the core flow region. This value was closed to channel bulk velocityU bulk =0.4 m/s measured using flow meters. The largest backward velocity was 0.068 m/s, obtained in left wall region where the swirling motion occurred.